Rembug Pelayanan Publik (RPM) Sebagai Aktualisasi Pelayanan Publik Berlandaskan Demokrasi Pancasila - Nuriyanto, Nuriyanto (Mahkamah Konstitusi Republik Indonesia, 2015)
Dynamic development of society, they want the public bureaucracy to be able to provide the public services more professional, effective, simple, transparent, open, timely, responsive and adaptive. With excellent public service, to build a human quality in the sense of increasing the capacity of individuals and communities to determine actively its own future. Actualization of democratic precepts in the public services delivery in Indonesia starting point on the importance of community participation ranging from formulating criteria for the services, how the delivery of the services, arranging each engagement, public complaints mechanism set up by the monitoring and evaluation of the implementation of the public services in order to co-together build a commitment to create quality of the public services. It’s all been contained in the Law 25 of 2009 on Public Services, certainly it has been based on the precepts of the democracy of Pancasila. Rembug of the public services as an actualization of the public services based on the democracy of Pancasila.